The Effect of Biochar Obtained from Municipal Pruning Wastes at Different Pyrolysis Temperatures on Maize Yield and Some Soil Properties - KAYIKCIOGLU, Huseyin Husnu; TEPECİK, Mahmut (MAS Journal of Applied Sciences, 2022)
The pot experiment was set up in a randomized plot design with three replications. Biochar wasobtained at three different pyrolysis temperatures (300, 500, 700°C) by using municipal pruning wastes. Inresponse to the biochar applications at five different doses (0, 10, 20, 30 and 60 t ha-1), some biological(soil respiration, dehydrogenase activity) and chemical properties of the soils (pH, electrical conductivityEC, organic carbon, cation exchange capacity-CEC, N, P, K, Ca, Mg, Na, Fe, Cu, Zn, Mn and B) and yield(fresh plant biomass) were investigated. The parameters analyzed showed significant changes between -48% and 141% when compared with the control soils (P<0.05). It was determined that the biochar obtainedat 300°C pyrolysis temperature can be biodegraded more easily than the biochar obtained at 500 and 700°C.Similarly, available phosphorus and boron had the most positive effect from biochar application at 300°Cpyrolysis temperature. Moreover, the available boron concentration achieved the highest increase with theapplication of 60 t biochar ha-1. It has been determined that biochar has the potential to increase the pHvalue of soils between 0.5-6.2% in 75 days. The EC value, which is an indicator of soil salinity, decreasedwith 700°C and 20, 30 and 60 t ha-1applications. An increase potential of 31.3% was determined in theCEC. There was no determinable effect on available Mn, Fe and Cu by independent variables. An increaseof 71.4% was detected in the maize yield with the application of 700 °C and 60 t ha-1.